BioMedical Engineering OnLine - Su, Fong-Chin; Foster, Kenneth R.
BioMedical Engineering OnLine is aimed at readers and authors throughout the world with an interest in using tools of the physical sciences to advance and understand problems in the biological and medical sciences. There are biomedical engineers in countries throughout the world, and the results of their work are scattered and often difficult to access. This publication promotes the rapid and free accessibility of articles for biomedical engineering researchers everywhere. The result is a worldwide community of biomedical engineers who are linked together by their various research interests and their values in promoting benefits to all of humanity.